Molecular Epidemiological Characteristics and Risk Factors for Acquiring HBV Among Li Ethnic in Baisha County, Hainan Island-Subgenotype D3 Was First Discovered in China - Xu, Ru; Song, Dandan; Wang, Min; Huang, Jieting; Liao, Qiao; Shan, Zhengang; Rong, Xia; Fu, Yongshui (Frontiers in Microbiology, 2022)
Our previous study showed that Baisha, a county on Hainan Island, is an endemic center for hepatitis C virus in the Li ethnic population, with significantly higher rates than in other parts of China. However, the epidemiology of HBV remains unclear. We conducted a comprehensive epidemiological survey of HBV in the Li ethnic population in which 1,682 volunteers were included from Baisha County. The seropositive rate for HBsAg was 10.2%. HBV-positive status was associated with the 20-40-year-old group (OR = 1.27, 95%CI 1.39-1.04, P<0.01) and alcohol consumption (OR = 2.97, 95%CI 2.03-4.33, P<0.01). Phylogenetic analysis showed that HBV subgenotype D3 (76 cases, 60.3%) was predominant in Baisha County which was first discovered in China, followed by C5 (25 cases, 19.8%), C1 (12 cases, 9.5%), B2 (10 cases, 7.9%), and undetermined subgenotypes (3 cases, 2.4%), which were significantly different from other geographical distribution of main genotypes in China. The most recent common ancestor (tMRCA) of the HBV genotype C in the Li ethnic of Baisha county was 1846 (95%CI:1739-1932), and Baisha-C5 was earlier than Baisha-C1 and Baisha-C2. Most D3 sequences were concentrated in one bundle and unrelated to those D3 genome sequences elsewhere in the world. According to the phylogenetic tree, D3 was introduced into Baisha County in 1884 (95%CI: 1816-1993) and became a local endemic virus. In conclusion, HBV infection in the Li ethnic group is characterized by high prevalence rates in 20-40-year-old individuals and a unique genotype distribution which were significantly different from other geographical distribution of main genotypes in China.